Evaluation of appendicitis risk prediction models in adults with suspected appendicitis. Issue 1 (3rd December 2019) - Bhangu, A.; ,
Abstract : Background: Appendicitis is the most common general surgical emergency worldwide, but its diagnosis remains challenging. The aim of this study was to determine whether existing risk prediction models can reliably identify patients presenting to hospital in the UK with acute right iliac fossa (RIF) pain who are at low risk of appendicitis. Methods: A systematic search was completed to identify all existing appendicitis risk prediction models. Models were validated using UK data from an international prospective cohort study that captured consecutive patients aged 16–45 years presenting to hospital with acute RIF in March to June 2017. The main outcome was best achievable model specificity (proportion of patients who did not have appendicitis correctly classified as low risk) whilst maintaining a failure rate below 5 per cent (proportion of patients identified as low risk who actually had appendicitis). Results: Some 5345 patients across 154 UK hospitals were identified, of which two‐thirds (3613 of 5345, 67·6 per cent) were women. Women were more than twice as likely to undergo surgery with removal of a histologically normal appendix (272 of 964, 28·2 per cent) than men (120 of 993, 12·1 per cent) (relative risk 2·33, 95 per cent c.i. 1·92 to 2·84; P  < 0·001). Of 15 validated risk prediction models, the Adult Appendicitis Score performed best (cut‐off score 8 or less, specificity 63·1 per cent, failure rate 3·7 per cent). The Appendicitis Inflammatory Response Score performed best for men (cut‐off score 2 or less, specificity 24·7 per cent, failure rate 2·4 per cent). Conclusion: Women in the UK had a disproportionate risk of admission without surgical intervention and had high rates of normal appendicectomy. Risk prediction models to support shared decision‐making by identifying adults in the UK at low risk of appendicitis were identified. Abstract : Women in the UK had a disproportionate risk of admission without surgical intervention and had high rates of normal appendicectomy. Risk prediction models to support shared decision‐making were identified by identifying UK adults at low risk of appendicitis. An online calculator is available (http://appy‐risk.org ). WCC, white cell count; CRP, C‐reactive protein; AIRS, Appendicitis Inflammatory Response Score; AAS, Adult Appendicitis Score. Important differences between men and women Abstract : Antecedentes: La apendicitis es la urgencia quirúrgica de cirugía general más frecuente en todo el mundo, pero su diagnóstico sigue siendo un desafío. El objetivo de este estudio fue determinar si los modelos de predicción de riesgo existentes pueden identificar de manera fiable a los pacientes del Reino Unido que se presentan en el hospital con dolor agudo en la fosa ilíaca derecha (right iliac fossa, RIF) con bajo riesgo de apendicitis. Métodos: Se realizó una búsqueda sistemática para identificar todos los modelos existentes de predicción de riesgo de apendicitis. Los modelos se validaron utilizando los datos del Reino Unido de un estudio International prospectivo de cohortes que incluía pacientes consecutivos de 16 a 45 años que se presentaron en el hospital con dolor agudo en RIF entre marzo y junio de 2017. El criterio de valoración principal fue la mejor especificidad que era posible alcanzar con el modelo (proporción de pacientes que no tenían apendicitis correctamente clasificados como de bajo riesgo) manteniendo una tasa de fracaso < 5% (proporción de pacientes identificados como de bajo riesgo que realmente tuvieron apendicitis). Resultados: Se identificaron 5.345 pacientes en 154 hospitales del Reino Unido, de los cuales dos tercios (67, 6%, 3.613/5.345) eran mujeres. Las mujeres tenían más del doble de probabilidades de someterse a una apendicectomía con un apéndice histológicamente normal (28, 2%; 272/964) en comparación con los varones (12, 1%; 120/993, riesgo relativo 2, 33 (i.c. del 95% 1, 92‐2, 84), P < 0, 001)). Entre los 15 modelos de predicción de riesgo validados, el sistema de puntuación de apendicitis en adultos (Adult Appendicitis Score) fue el que obtuvo la mejor predicción (punto de corte ≤ 8, especificidad 63%, tasa de fracaso 3, 7%). El sistema de puntuación de la respuesta inflamatoria de apendicitis (Appendicitis Inflammatory Response Score) fue el que obtuvo la mejor predicción en los varones (punto de corte ≤ 2, especificidad 25%, tasa de fracaso 2, 4%). Conclusión: Las mujeres del Reino Unido tuvieron un riesgo desproporcionado de ingreso sin intervención quirúrgica, así como porcentajes elevados de apendicectomías blancas. Se encontraron modelos de predicción de riesgos para apoyar la toma de decisiones compartida mediante la identificación de adultos del Reino Unido con bajo riesgo de apendicitis.